(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The article focuses on the relevance and current state of the dendrosozological direction development in synphytosozological research. It based on a significant scientific author’s work, above all, a number of monographic editions about the rare dendrodiversity of the Natural Reserve Fund within Forest-Steppe, Steppe and Polissya of Ukraine. Therefore, this publication presents the results of research for the Broadleaf Forests zone of Ukraine. In the article, authors described the essence of the methodology of inventory research of phytocenotic dendrodiversity. The determination of synphytososological categories, classes and indices were carried out using the method of integral synphytososological evaluation in rare dendrophytocenoses. The obtained results of synphytosozological analysis indicate that the protected rare dendrophytocenofond of the Broad Leaved Forests zone of Ukraine is represented by four types of vegetation: marsh (forest and shrubland swamps), forest (deciduous and coniferous forests), shrub and steppe (shrub steppes). These types of vegetation cover 15 formations, 45 subformations and 128 associations. Syntaxonomically the most diversified formation is Querceta roboris (38 associations). The majority of dendrosozophytocenoses are located in the extreme northeastern boundaries of distribution with a rare type of association. The vast majority of associations belong to the Berne Convention, just over half of them are listed in the current official publication of the Green Data Book of Ukraine, and only 16 % have been taken to the Regional Green Data Book of the Western regions of Ukraine. The core of rare associations has predominantly average outcomes of the outphytosozological categories (second), classes (II) and indices (10.5). Majority of the rare syntaxons are tied to nature reserves and national natural parks, but 20 associations are still not reserved, probably 5 of them have already disappeared from the research area.